IGBT Real-time Junction Temperature Calculation Based on Converter Operation Data - LI Yanyong; XIN Li; LAI Wei; LIU Wenye; FU Hangjie; WANG Liping (Kongzhi Yu Xinxi Jishu)
In order to evaluate IGBT operation junction temperature of locomotive operation and provide the basis for IGBT health status and life prediction, a real-time junction temperature calculation method was proposed based on the average power loss of each fundamental period from output phase voltage and current of converter. A corresponding calculation program of temperature junction was developed, and performance of the proposed method was compared with PLECS electro-thermal simulation. The results showed that the proposed method not only can calculate junction temperature of different conditions accurately, but also can calculate junction temperature conveniently without knowing parameters of the control strategy and quantity limitation of loading cycles, and it is suitable for IGBT junction temperature calculation with different operation working conditions of converter in engineering application.